RESPON ISLAM TERHADAP PERUBAHAN SOSIAL - Mohammad Deny Irawan (TAJDID: Jurnal Ilmu Ushuluddin, 2018)
As a universal religion, Islam has promised social change in society. Even so, a number of Muslim and Islamic scholars have also admitted that Islam has all the conditions to rise and color the social life of the world community. This article will explain the Islamic response to social change in society, including the role of fatwa as ijtihad products. Religion and Social still get space in the community. At least there are 3 bargaining power positions that are given between religion and society, namely: Religious affairs are more dominant, community affairs are more dominant and compromise between religion and social society in the frame of religion and social frame. This certainly shows that religion as a response to social change as a win-win solution to community life. Sebagai agama universal, Islam telah menjanjikan perubahan sosial di masyarakat. Pun demikian dengan sejumlah cendekiawan muslim serta Islamolog ikut mengakui jika Islam memiliki segala syarat untuk bangkit dan mewarnai kehidupan sosial masyarakat dunia. Artikel ini akan menjelaskan tentang respon Islam terhadap perubahan sosial masyarakat termasuk juga perani fatwa sebagai produk ijtihad. Agama dan Sosial masih mendapatkan ruang di masyarakat. Setidaknya ada 3 posisi daya tawar yang diberikan antara agama dan masyarakat, yaitu: Urusan agama lebih dominan, urusan masyarakat lebih dominan dan kompromi antara agama dan sosial kemasyarakatan dalam bingkai agama maupun bingkai sosial. Hal ini tentunya menunjukan bahwa agama sebagai respon perubahan sosial sebagai win win solution kehidupan bermasyarakat.